Training on organic waste processing into liquid fertilizer using EM4 in Tundagan Hamlet - Lisdinawati, Putri Dzakiyya (Jurnal Abmas, 2026)
Household waste management that remains suboptimal, particularly the practice of open waste burning, continues to pose environmental and public health challenges in rural areas. In Tundagan Hamlet, Batulawang Village, Banjar City, this habit contributes to air pollution and increases the risk of Acute Respiratory Infections (ARI). This community service program aimed to enhance community knowledge and skills in managing organic waste by converting it into liquid organic fertilizer using natural EM4 technology as an environmentally friendly alternative to burning. The novelty of this program lies in integrating technical training on organic waste processing with a promotive-preventive environmental health approach explicitly linked to ARI risk reduction, supported by quantitative evaluation through pre-test and post-test analyses. The program was implemented through lectures, interactive discussions, and hands-on practice integrated with the Field Learning Practice (PBL 2) of Public Health students, involving 25 participants. Wilcoxon test results indicated a significant increase in knowledge, with 17 participants showing improved scores and none declining. The program strengthens community capacity, promotes environmental health, and offers potential economic benefits through the use and marketing of liquid organic fertilizer.
Keywords: community empowerment; EM4 technology; liquid organic fertilizer; organic waste management